Pengembangan Modul Fisika Berbasis Predict-Observe-Explain (POE) dengan Memanfaatkan QR Code dan Video Pembelajaran YouTube - Rahman Sidik; Neng Nenden Mulyaningsih; Irnin Agustina Dwi Astuti (NUCLEUS, 2021)
Most of the students stated that studying Physics using relatively thick textbooks tended to be boring. This has an impact on unsatisfactory learning outcomes. The purpose of this research is to develop a product in the form of a module that is compiled using the Predict-Observe-Explain (POE) learning model with a combination of learning videos from YouTube, and analyze the feasibility level. The research method used is by making a module on temperature and heat material, which includes learning videos in the form of a QR code that can be scanned via a smartphone. The parameters analyzed include the results of the validation of experts who include material experts, media experts, and linguists. Another parameter that was measured as the level of student interest in the module, with a sample of 10 students from SMAN 1 Dramaga, SMA Bumi Sejahtera, and SMA Hanura. The results showed that the assessments of material experts, media experts, and linguists respectively were 3.83, 3.32, and 3.47 with the criteria of "very decent". The attractiveness test results for SMAN 1 Dramaga, SMA Bumi Sejahtera, and SMA Hanura were 3.57, 3.36 with the criteria of "very interesting" and 3.03 with the criteria of "attractive". Thus, it is concluded that the POE-based physics module by utilizing the QR code and YouTube learning videos is very feasible to be used as a learning medium.